Digital Marketing, Service Quality, and Customer Loyalty in Indonesian Retail with the Moderating Role of Consumer Lifestyle - Erlina Puspitaloka Mahadewi; Zairil Zairil; Arnastya Iswara Sanantagraha; Suryari Purnama (Jurnal Manajemen Industri dan Logistik, 2025)
This research aims to analyze the influence of digital marketing strategies and service quality on customer loyalty and repeat purchase decisions in the retail industry in Indonesia with the moderating role of consumer lifestyle. This research uses quantitative methods with descriptive and explanatory approaches. survey research methods. The technique used in this research was purposive sampling. The research results show that the digital marketing variable has no significant effect on customer loyalty at retail companies in Indonesia, service quality has a positive and significant effect on customer loyalty at retail companies in Indonesia, digital marketing and service quality has a positive and significant effect on repurchase decisions at retail companies in Indonesia, but customer loyalty has no effect on consumer lifestyles, and repurchase decisions have a positive and significant effect on consumer lifestyles.